Thermal conductivity features of ZnO-based varistors using the laser-pulse method - Barrado, C. M.; Leite, E. R.; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
The thermal conductivity of several commercial ZnO-based varistor systems was determined based on the laser-pulse method, a technique that proved extremely useful and easy to apply. Using this technique, the thermal conductivity was found to be dependent on the microstructural features of the devices, involving the mean grain size and phase composition. Among the phases existing in commercial ZnO-based varistors, ZniSb2O12 and Bi2O3 were found to contribute strongly to the thermal conductivity of the devices. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ZnO; varistors; thermal conductivity